Analysis of the free amino acid content in pollen of Bangladeshi common fruits flower of known allergenic activity - Ranajit Kumar Shaha (International Research Journals, 2012)
The free amino acid content of aqueous extracts (preserved in 50 % glycerol) of pollen of Bangladeshi five (5) common fruits flower of the Asteraceae family three, i.e. Mangifera indica L, Pistacho and Cashew; Sapindaceae family one flower i.e. Litchi chinensis and Vitex glabrata family one flower i.e. Blackberry has been investigated using a thin-layer chromatographic technique. The amino acid content was found to vary from 0.75 to 2.25% of the total dry weight of pollen was estimated by a powerful oxidising agent (ninhydrin reagent). Thirteen amino acids were identified, among them n-butyric acid, proline and aspartic acid were present in almost all different pollen samples. The other major amino acids present in free from included alanine, cystine, arginine, glutamic acid, isoleucine, glycine, leucine, methonine, tryptophan and tyrosine. α-Alanine, γ-amino-n-butyric acid, glycine, dl-leucine, l-lysine, l-proline and dl-serine were identified. No species differences were detected and there was no difference between the viable and non-viable pollen extracts examined.